Acoustic optimization of curved architecture in practice: The new Strait Cultural Arts Center in Fuzhou. Issue 3 (September 2021) - Jurkiewicz, Yann; Moller, Henrik; Wulfrank, Thomas; Wang, Jingbo; Kahle, Eckhard
Curved surfaces are increasingly part of the architectural language used in buildings for the performing arts, yet have known challenges both in reality and in ray-tracing-based computer simulations. The designs of the 1000-seat symphony hall, the 1600-seat opera house and the 800-seat multi-purpose hall in Fuzhou, China, were all based on curved surfaces, both convex and concave, often covered with local ceramic tiles. Providing the right amount, distribution and quality of early reflections thus required a precise analysis of the acoustic behavior of curved surfaces. The acoustic design interacted with the architecture in precisely shaping those curves in 3D. In order to explore the acoustic potential and detect problems related to the architectural concept of both rooms, novel geometrical acoustics analysis algorithms were developed within NURBS modeling software rather than relying on commercial ray-tracing algorithms. Optimization of the curved surfaces is obtained when the output of these algorithms, the interpretation of the acoustic consultant, and the required integration of acoustic solutions within the global architectural concept are all aligned – a "meeting of minds" between acoustics and architecture. The analysis procedure and geometrical acoustics algorithms used will be presented in detail, as well as the related decision-making process, the acoustic predictions and the measurement results of the three built halls.